npj Autoimmunity - Canavan, Mary.; Willis, Alexandra; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Autoimmunity is an internationally peer-reviewed, open-access, community-focused journal dedicated to advancing our understanding, diagnosis, and treatment of autoimmune diseases. The journal publishes hight-quality work that deepens our understanding of immune dysregulation and its clinical manifestations across wide spectrum of autoimmune conditions including Inflammatory Bowel Disease, Rheumatoid arthritis Type 1 diabetes, Psoriasis, Systemic lupus erythematosus, Guillain-Barre syndrome, Multiple sclerosis, Chronic inflammatory demyelinating polyneuropathy, Graves, Hashimoto's thyroiditis, Scleroderma, Ankylosing spondylitis, Vasculitis. The journal covers a broad range of topics including but not limited to: Clinical Autoimmunity (Including diagnosis, biomarkers, patient management, autoimmune diseases, clinical trials) Molecular and Genetic Mechanisms of Autoimmunity (including GWAS, epigenetics, single-cell omics, autoantibodies, genetic risk) Preclinical and Basic Autoimmunity (including novel animal models, immune signalling, immunoregulation and immunological tolerance) Translational Immunology and Therapeutics (including novel immunotherapies, CAR therapy, tolerogenic vaccines, biologics and small molecule inhibitors) Microbiome and Environmental Triggers of Autoimmunity (including gut microbiota, infections, diet, pollutants, autoantigen exposure) The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by experts in basic, clinical and translational autoimmunity who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Immunology; Immunologic diseases; Autoimmunity; Rheumatology; Immunology; Immunological Disorders; Autoimmunity; Rheumatology